Operational Improvement in Aquaculture: DMAIC Strategies to Optimize Distribution Costs for Exporting Companies - Quevedo Olaya, Jhonsson Luis (2024)
In this study, the aim was to reduce the distribution costs in an aquaculture company, which, after an initial assessment, were found to be excessively high with an uncontrolled statistical distribution. The initial approach focused on distribution costs per service provided, employing the DMAIC methodology as the primary improvement tool. This technique aided in breaking down effects and symptoms to identify the root causes of the issues, enabling the suggestion and implementation of improvements such as standardization of the order handling process, enhancement of communication channels, innovative recruitment strategies, and theoretical and practical training. These measures significantly improved the work environment, involving a more committed team and processes that were clearly established and aligned with the company's needs. Regarding distribution costs, there was a reduction from an average of 8,819 soles to 8,042 soles, along with achieving a more reduced and orderly statistical variability.